Bilirubin-induced immunostimulant effects and toxicity vary with neural cell type and maturation state - Falcao, AS (2015)
Hyperbilirubinemia remains one of the most frequent clinical diagnoses in the neonatal period. The increased vulnerability of premature infants to unconjugated bilirubin (UCB)-induced brain damage may be due to a proneness of immature nerve cells to UCB-t